O paradigmático caso do processo às juntas militares argentinas - Barrientos-Parra, Jorge David [UNESP] (Instituto Educacional Piracicabano da Igreja Metodista, 2014)
This article analyzes the case of the proceedings against Argentina’s Military Juntas that led to jail those responsible for heinous crimes committed during the military dictatorship. The said proceeding has a high symbolic value in the struggle for human rights in Latin America and is relevant and timely in Brazil where the right to the truth regarding the missing people during the military dictatorship is in debate, as well as the invalidation of the Amnesty Act regarding the common crimes of torture, rape and / or kidnapping, among others. In the case of Argentina, following Roxin’s doctrine of mediate authorship, the Court held that the crimes were committed by the military through the use of an organized power apparatus and emphatically dismissed allegations that such crimes were justified in the so-called “dirty war”. Thus, the case against the Military Juntas has become a paradigmatic one, not only in Argentina, where many military leaders had to respond to criminal actions, but for all countries in the region that faced similar situations in recent history.

Este artigo pretende analisar o caso do processo contra as juntas militares argentinas que levou ao cárcere os responsáveis por crimes hediondos praticados durante o período da ditadura militar. O referido processo tem um alto valor simbólico na luta pelo respeito aos direitos humanos na América Latina e ganha relevância e atualidade no Brasil quando se discute a questão do direito à verdade envolvendo o tema dos desaparecidos na época do regime militar e o debate sobre a invalidação da Lei de Anistia (Lei No 6.683, de 28 de agosto de 1979) no que tange aos crimes comuns de tortura, violação e/ou sequestro, entre outros. No caso argentino, o Tribunal, seguindo a doutrina de Roxin da autoria mediata, considerou que os crimes foram cometidos pelos militares mediante a utilização de um aparato organizado de poder e afastou, de maneira enfática, as alegações de que os delitos teriam justificação na denominada “guerra suja”. Nesse sentido, este processo contra as juntas militares passou a ser um caso paradigmático, não somente na Argentina, em que muitos chefes militares tiveram que responder a ações criminais, mas para todos os países da região, que enfrentaram situações semelhantes em sua história recente.
The paradigmatic case of the legal proceeding against Argentina’s Military Junta
Keywords: Human rights; Criminal procedings; Argentina; Military juntas; Judgments; Mediate authorship; Direitos Humanos; Argentina; Juntas militares